2020
DOI: 10.15578/squalen.v15i3.511
|View full text |Cite
|
Sign up to set email alerts
|

Golden Sea Cucumber: Identification and the Antioxidant Activity of Its Collagen Hydrolysates

Abstract: Golden sea cucumber or locally known as “teripang emas” is one of Indonesia’s most popular sea cucumber and widely processed as functional food or supplement due to its bioactivities. The sea cucumber is often misidentified due to its morphological similarities with other Stichopus spp. This study aimed to identify the golden sea cucumber obtained from West Nusa Tenggara, Indonesia, by a molecular method and study the antioxidant activities of its collagen hydrolysates. The hydrolysates were produced by hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…In particular, Neutrase-derived hydrolysate produced four bioactive peptides and showed strong DPPH radical-scavenging activity, suggesting that it was related to the presence of hydrophobic amino acids in their sequences and low molecular weights (<1 kDa). Similarly, collagen hydrolysates (molecular weight 14.4 to 25 kDa) obtained from golden sea cucumber revealed strong DPPH radical scavenging activity, where Neutrase was used to start the hydrolysis [ 59 ]. García et al [ 34 ] designed novel functional food products using protein hydrolysate (Protamex and Alcalase) obtained from Parastichopus tremulus and Holothuria forskali , which demonstrated antioxidant, antihypertensive, and anti-inflammatory properties, especially those obtained from H. forskali .…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…In particular, Neutrase-derived hydrolysate produced four bioactive peptides and showed strong DPPH radical-scavenging activity, suggesting that it was related to the presence of hydrophobic amino acids in their sequences and low molecular weights (<1 kDa). Similarly, collagen hydrolysates (molecular weight 14.4 to 25 kDa) obtained from golden sea cucumber revealed strong DPPH radical scavenging activity, where Neutrase was used to start the hydrolysis [ 59 ]. García et al [ 34 ] designed novel functional food products using protein hydrolysate (Protamex and Alcalase) obtained from Parastichopus tremulus and Holothuria forskali , which demonstrated antioxidant, antihypertensive, and anti-inflammatory properties, especially those obtained from H. forskali .…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…The test results showed that H. leucospilota had the best antioxidant activity of 11.12% at a dose of 1.0 mg/ml extract. Other research showed that collagen hydrolysate of S. horrens had an IC50 value of 5.25 mg/ml to DPPH free radicals [21].…”
Section: Resultsmentioning
confidence: 94%
“…Previous research regarding hydrolyzed collagen derived from golden sea cucumbers has an antioxidant effect (IC50 of 5.25±0.15 mg/ml) [9]. Other studies confirm that sea cucumbers are a source of collagen and need further research [10].…”
Section: Introductionmentioning
confidence: 92%